Further discoveries on the minuscule spiders from the Chocó region of Ecuador with the description of seven new species of Anapis (Araneae: Anapidae) - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2018)
The diversity of the small Araneoidea spider family Anapidae from the Chocó region of Ecuador is examined. A total of 325 Anapidae specimens were collected from which seven new species all from the genus Anapis were discovered and herein described: Anapis anabelleae n. sp., A. carmencita n. sp., A. churu n. sp., A. mariebertheae n. sp., A. naranja n. sp., A. nawchi n. sp. and A. shina n. sp. Furthermore, the male of Anapisona pecki Platnick & Shadab 1979 is described for the first time, and new locality data are provided for Anapis chiriboga Platnick & Shadab 1978 and Pseudanapsis domingo Platnick & Shadab 1979.